EDUCATIONAL QUALITY ISSUES IN THE PROCESS OF IMPLEMENTING DIGITAL TECHNOLOGIES IN THE MODERN EDUCATIONAL SYSTEM (Universal International Scientific Journal, 2026)
. This article analyzes the problems associated with the quality of education in the process of introducing digital technologies into the modern education system. The study highlights the role of digital technologies in the educational process, their impact on pedagogical activity, and their potential for increasing educational efficiency. It also substantiates the importance of the human factor in the educational process and the need to develop the digital competence of teachers.
Keywords: digital technologies, quality of education, modern education system, pedagogical skills, digital competence, innovative education, digitalization of the educational process.